Transformational and Transactional Leaders; a Case Study in the Higher Education - Varol, Asaf; Varol, Serkan (Acad Conferences Ltd, 2012)
Understanding and analyzing the difference between transformational and transactional leadership is crucial in getting the whole concept of leadership theories in organizations. Transformational leadership is the most popular theory which has evolved from the elements of leadership such as traits, situational and transactional leadership that focuses on the role of organization and group performance. In transactional leadership, rewards and punishments are contingent upon the performance of the followers. On the other hand, transactional leadership makes clear that what is required and expected from their subordinates. If subordinates perform well, they receive reward. When they don't perform well, a punishment may apply. This method is not very often used in organizations In this research, first we have compared the transformational and transactional leadership theories and their applicability to the higher education institutions by integrating the characteristics of each model into the single instructor and having him to apply the assigned techniques to the class. Secondly, based on performance-productivity metrics and examination results, we have found that both transformational and transactional leadership techniques have their own strengths and weaknesses. Therefore, in this paper we proposed a hybrid approach which combines the best of each technique, which also provided better performance and productivity results. The findings are also deeply interpreted.
9th International Conference on Intellectual Capital, Knowledge Management and Organisational Learning (ICICKM) -- OCT 18-19, 2012 -- Univ Rosario, Bogota, COLOMBIA
Keywords: transformational and transactional leaders; management of higher education; leadership